Pengaruh Persepsi Pengguna E-Wallet terhadap Pembelian Impulsif: Peran Mediasi Kepuasan dan Kesenangan - Nofa Ardhan Sultoni; Alldila Nadhira Ayu Setyaning (Penerbit Goodwood, 2025)
Purpose: This study aims to determine the influence of interactivity perception, risk perception, visual appeal, and subjective norms on impulse purchase behavior, with satisfaction and perception of pleasure as intervening variables in e-wallet users in Indonesia. Methodology/approach: The approach used in this study is a quantitative approach. The data collection technique was by distributing online questionnaires to 300 respondents using Google Form. The sampling technique used a non-probability sampling technique using the purposive sampling method which was then processed using structural equation modeling SEM (Structural Equation Modeling) using the PLS program. Results/findings: This study found that the perception of interactivity, visual appeal, and subjective norms had a positive and significant effect on satisfaction and perception of pleasure. On the other hand, risk perception has a negative and significant effect on both. In addition, satisfaction and perception of pleasure also have a positive and significant effect on impulse buying behavior. Conclusions: Overall, the study confirms that both cognitive (satisfaction) and affective (enjoyment) responses play a crucial mediating role in transforming external stimuli into impulsive purchase decisions. The findings strengthen the application of the S-O-R framework in the digital financial context and provide both theoretical enrichment and managerial implications. Limitations: The limited number of respondents and the variables used were limited to perceived interactivity, perceived risk, visual appeal, subjective norms, satisfaction, and perceived enjoyment. Contribution: This study contributes to policymaking for e-wallet service providers in designing more effective marketing strategies focused on user experience.